What the Old Testament Can Contribute to an Understanding of Divine Creation. - Miller, Robert (Heythrop Journal, 2019)
The article discusses how the Old Testament can contribute to an understanding of divine creation. It mentions that the Catholic Church had bypassed the science vs. faith controversy that plagued Protestantism. It also reveals that Protestant Neo-Orthodox theology had already surrendered understanding of the empirical world and of cosmology to scientists.